Pengembangan Kemampuan Motorik Halus Melalui Kegiatan Menjiplak - Reviana Reviana; Meliarni Meliarni; Rina Rina (LPPI Yayasan Almahmudi bin Dahlan, 2023)
This study was motivated by low fine motor skills in group B children in Terang Bulan Islamic Kindergarten, Bangun Purba Timur Jaya Village. One solution to this problem is to apply plagiarizing activities, this study aims to improve fine motor skills in group B at TK Islam Terang Bulan Desa Bangun Purba Timur Jaya. The method used in this study is the Classroom Action Research (PTK) method. This class action research is carried out as many as 2 cycles, in each cycle there are 2 meetings. Data collection techniques used observation and documentation. The results of this study showed an increase in children's scores from pre-action, it was known that the BB value in pre-action was 10 children or 75%, then in cycle 1 it became 6 children or 60% then in cycle II it became 0 children or 0%. MB value in pre-action 4 children or 24.90%, then in cycle 1 to 2 children or 18.18% in cycle II to 0children or 0%. The BSH value in the actions was 1 child or 9.09%, then in cycle 1 it became 3 children and in cycle II it became 4 children or 29.27%. The BSB value in preaction 0 children or the next 0% in cycle 1 became 4 children or 29.27% and in cycle II there were 8 children or 72.73%. Based on the results of the above research, the researcher suggested to teachers to make the activity as an alternative activity in improving children's fine motor. Keywords: Fine Motor, Cramping activities, classroom action research.